Hypertension in kidney transplantation: a consensus statement of the 'hypertension and the kidney' working group of the European Society of Hypertension. Issue 8 (August 2021) - Halimi, Jean-Michel; Ortiz, Alberto; Sarafidis, Pantelis A.; Mallamaci, Francesca; Wuerzner, Grégoire; Pisano, Anna; London, Gérard; Persu, Alexandre; Rossignol, Patrick; Sautenet, Bénédicte; Ferro, Charles; Boletis, John; et al.
Abstract : N/A: Hypertension is common in kidney transplantation recipients and may be difficult to treat. Factors present before kidney transplantation, related to the transplantation procedure itself and factors developing after transplantation may contribute to blood pressure (BP) elevation in kidney transplant recipients. The present consensus is based on the results of three recent systematic reviews, the latest guidelines and the current literature. The current transplant guidelines, which recommend only office BP assessments for risk stratification in kidney transplant patients should be reconsidered, given the presence of white-coat hypertension and masked hypertension in this population and the better prediction of adverse outcomes by 24-h ambulatory BP monitoring as indicated in recent systematic reviews. Hypertension is associated with adverse kidney and cardiovascular outcomes and decreased survival in kidney transplant recipients. Current evidence suggests calcium channel blockers could be the preferred first-step antihypertensive agents in kidney transplant patients, as they improve graft function and reduce graft loss, whereas no clear benefit is documented for renin–angiotensin system inhibitor use over conventional treatment in the current literature. Randomized control trials demonstrating the clinical benefits of BP lowering on kidney and major cardiovascular events and recording patient-related outcomes are still needed. These trials should define optimal BP targets for kidney transplant recipients. In the absence of kidney transplant-specific evidence, BP targets in kidney transplant recipients should be similar to those in the wider chronic kidney disease population.